QUATERNARY GLACIATION OF NORTH-EASTERN ASIA - Zamoruyev V. (My University, 2004)
This chapter explores that northeastern Asia is a region with a very diverse, mostly mountainous topography. The territory has a frigid continental climate, with great diurnal and seasonal fluctuations of air temperatures and low precipitation, most of which occurs as rain in the frost-free part of the year. Because of the severe climate, the most common vegetation types are taiga, forest tundra, and tundra. Permafrost occurs almost everywhere. Modern glaciers are confined to the highest mountains and are rather small. No palaeobotanical evidence for drastic changes of vegetation throughout the quaternary is known. This suggests that the climate was stable and that climatic fluctuations did not result in major environmental changes. It follows that the main features of today's glaciers were also characteristic for the glaciers of the past. A specific feature of glaciation in northeastern Asia was a sharp distinction between the area of today's glaciers and that during the Pleistocene. Most of the glaciated parts of northeastern Asia are mountain ranges only of medium height. As soon as the climate became cooler, vast areas found themselves above the snow line and became the accumulation areas for glaciers. However, under a cooler climate, the share of snow was much increased, and as a consequence the accumulation area expanded enormously, giving rise to extensive glaciation. It is most likely that the late Pleistocene was not only the time of maximum cooling, but also the time of the most extensive glaciation. The chapter explains that the identification of traces of pre-late Pleistocene glaciations is required. Reported traces of supposedly pre-late Pleistocene glaciations need to be checked in the field.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная